2018
DOI: 10.12681/jhvms.16077
|View full text |Cite
|
Sign up to set email alerts
|

Τhe first report of Linguatula serrata in grey wolf (Canis lupus) from Central Balkans

Abstract: Linguatula serrata is a cosmopolitan, bloodsucking parasite found in both domestic and wild animals. Humans are not considered as its main hosts but can act as both intermediate (visceral linguatuliasis) and final hosts (nasopharyngeal linguatuliasis). Reports on wild canids as definitive hosts of this parasite are scarce. During 2009-2011 the autopsy was performed on 42 legally hunted grey wolves (Canis lupus) from Serbia and Former Yugoslav Republic of Macedonia (FYROM). Only one specimen was infected with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Linguatula serrata has previously been reported from wolves in Romania (Gherman et al 2002 ) as well as neighboring areas of the Balkans (Pavlović et al 2017 ) and Greece (Diakou et al 2014 ; Liatis et al 2017 ). Gherman et al ( 2002 ) reported 42.8% of wolves to be infected, compared to 17.5% in this study; the wolves examined by them were all collected from the same geographical area in central Romania, compared to the much wider geographical distribution examined in this study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Linguatula serrata has previously been reported from wolves in Romania (Gherman et al 2002 ) as well as neighboring areas of the Balkans (Pavlović et al 2017 ) and Greece (Diakou et al 2014 ; Liatis et al 2017 ). Gherman et al ( 2002 ) reported 42.8% of wolves to be infected, compared to 17.5% in this study; the wolves examined by them were all collected from the same geographical area in central Romania, compared to the much wider geographical distribution examined in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Linguatula serrata is also commonly reported in dogs within the same regions of Romania (Negrea et al 2009 ) and the Balkans (Pavlović et al 2017 ). Pavlović et al ( 2017 ) reported that the prevalence of infection of L. serrata in dogs in urban areas of the Balkans had dramatically reduced from the 1930s to much lower levels now.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Italy, the adult form of the parasite was recently observed in a client-owned dog with nasal carcinoma [27] and previously in stray dogs living in suburban areas [28,29], where they likely become infested by eating contaminated rodents and/or domestic ruminants. Recently, a study carried out on 42 legally hunted gray wolf in Serbia and North Macedonia evidenced parasite infestation in the nasal cavity of a gray wolf from the central Balkans [30]. The visceral linguatulosis by immature forms of the parasite was commonly observed in slaughtered cattle in different European countries, such as Great Britain [31], France [32], and Italy, where the parasitosis was often detected in cattle and sheep during the first half of the 20th century [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies of wolf-parasite associations are particularly important as emerging findings from Europe and North America have revealed new infections and spatial changes in parasitism of wolves (Beck et al, 2017;Ćirović et al, 2015;Hermosilla et al, 2017;Molnar et al, 2015Molnar et al, , 2019Pavlović et al, 2018) as well as in other canids (Fuehrer et al, 2016). Given that canids host several zoonotic parasites, changing host-parasite relationships could have major implications for both ecosystem and public health (Cerda et al, 2018;Tasić-Otašević et al, 2016).…”
Section: Introductionmentioning
confidence: 99%